Selenoprotein S ablation-mediated pyroptosis contributes to liver damage resulting from selenium deficiency in chickens - Huanqi Zhang; Xiaozhe Chen; Tingjin Lu; Qiyuan Cao; Xiaojing Li (Poultry Science, 2025)
Selenium is an essential trace element for the synthesis of selenocysteine. Selenoprotein S (SELS) acts as a carrier protein for selenium and exhibits anti-inflammatory properties. However, the role of the SELS in selenium deficiency remains unclear. This study aimed to investigate the role of SELS in selenium deficiency-mediated pyroptosis. A selenium-deficient chicken model was established using a low-selenium diet, allowing for analysis of the pyroptosis markers GSDMD and NLRP3 by immunohistochemistry and the expression levels of 25 selenoproteins in the liver. The results show that the selenium-deficient diet increased the levels of NLRP3 and GSDMD while reducing the expression of nine selenoproteins (DIO1, GPX1, GPX6, TXRD2, SELF, SELN, SELO, SELS, and SELT). SELS ablation abolished the activities of antioxidant enzymes, leading to excessive production of ROS and MDA. In addition, SELS knockdown activated the NF-κB pathway and induced pyroptosis. Following transfection, the introduction of N-acetylcysteine, BAY11-7082, or MCC950 alleviated the pyroptosis induced by SELS knockdown. However, MCC950 did not affect the NF-κB pathway, and both BAY 11-7082 and MCC950 were ineffective in reducing ROS accumulation. In conclusion, SELS deficiency leads to ROS generation and activation of the NF-κB pathway activation, ultimately inducing pyroptosis and the release of inflammatory factors.